Vertical Migration of Pelagic and Mesopelagic Scatterers From ADCP Backscatter Data in the Southern Norwegian Sea - Boris Cisewski; Hjálmar Hátún; Inga Kristiansen; Bogi Hansen; Karin Margretha H. Larsen; Sólvá Káradóttir Eliasen; Jan Arge Jacobsen (Frontiers in Marine Science, 2021)
Records of backscatter and vertical velocity obtained from moored Acoustic Doppler Current Profilers (ADCP) enabled new insights into the dynamics of deep scattering layers (DSLs) and diel vertical migration (DVM) of mesopelagic biomass between these deep layers and the near-surface photic zone in the southern Norwegian Sea. The DSL exhibits characteristic vertical movement on inter-monthly time scales, which is associated with undulations of the main pycnocline between the warm Atlantic water and the underlying colder water masses. Timing of the DVM is closely linked to the day-night light cycle—decent from the photic zone just before sunrise and ascent immediately after sunset. Seasonal variations are also evident, with the highest DVM activity and lowest depth averaged mean volume backscatter strength (MVBS) during spring. This suggests that both oceanographic and optical conditions are driving the complex dynamics of pelagic and mesopelagic activity in this region. We hypothesize that the increased abundance of calanoid copepods in the near-surface layer during spring increases the motivation for vertical migration of pelagic and mesopelagic species, which therefore can explain the increased DVM activity during this season.